Models for Education Worship in Early Childhood on Parenting Activities in Raudhatul Athfal Aisyah Az-Zahra - Masganti Sit; Sholihah Titin Sumanti; Juniawati Suza (Britain International for Academic Research (BIAR) Publisher, 2020)
This study aims to determine the implementation of early childhood worship education in parenting activities in RA Aisyah Az-Zahra and develop steps to develop models of worship education in parenting activities. Although the focus of research is on RA Aisyah Az-Zahra. This research uses the Research and Development (R&D) method. Mass product is the final product which is carried out by providing research results in the form of research reports in the form of journals and modules in the form of manuals and then disseminated by publishing journals and publishing modules. The product produced in this study is a parent guide module for early childhood worship education models.